2013
DOI: 10.2174/1874091x01307010044
|View full text |Cite
|
Sign up to set email alerts
|

Different Redox Response Elicited by Naturally Occurring Antioxidants in Human Endothelial Cells

Abstract: Evidences that higher natural antioxidant (NA) intake provides protection against cardiovascular disease (CVD) are contradictory. Oxidative-induced endothelial cells (ECs) injury is the key step in the onset and progression of CVD and for this reason the cellular responses resulting from NA interaction with ECs are actively investigated. This study was designed to investigate the direct impact of different naturally occurring antioxidants on the intracellular ROS levels in cultured human ECs. NA-induced redox … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
37
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 32 publications
2
37
0
5
Order By: Relevance
“…Evidences showed that antioxidants could turn into prooxidants under certain concentrations and/or intracellular redox states. 66 It was reported that coumaric acid and resveratrol were antioxidants at high cellular ROS levels but acted as pro-oxidants as the cellular ROS level was low. 66 Moreover, dietary phenolic is often considered as an antioxidant, but the presence of oxygen or transition metals might catalyze its redox cycling and in turn lead to the production of phenoxyl radicals.…”
Section: E Comparison Between Circulating and Static Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidences showed that antioxidants could turn into prooxidants under certain concentrations and/or intracellular redox states. 66 It was reported that coumaric acid and resveratrol were antioxidants at high cellular ROS levels but acted as pro-oxidants as the cellular ROS level was low. 66 Moreover, dietary phenolic is often considered as an antioxidant, but the presence of oxygen or transition metals might catalyze its redox cycling and in turn lead to the production of phenoxyl radicals.…”
Section: E Comparison Between Circulating and Static Conditionsmentioning
confidence: 99%
“…66 It was reported that coumaric acid and resveratrol were antioxidants at high cellular ROS levels but acted as pro-oxidants as the cellular ROS level was low. 66 Moreover, dietary phenolic is often considered as an antioxidant, but the presence of oxygen or transition metals might catalyze its redox cycling and in turn lead to the production of phenoxyl radicals. 67 Therefore, to test the antioxidant or pro-oxidant effect of a specific compound under a certain concentration, it is necessary to create an intracellular redox state close to the in vivo condition.…”
Section: E Comparison Between Circulating and Static Conditionsmentioning
confidence: 99%
“…При этом существенна окислитель-ная модификация клеток сосудистого эндотелия, приводящая к развитию эндотелиальной дисфункции (ЭД) [11]. В условиях инсульта формирование ЭД при-водит к ухудшению церебральной микроциркуляции, повышенному тромбообразованию, индукции воспале-ния и пролиферации сосудистой стенки, что усугубляет течение заболевания и снижает шансы на его благо-приятный исход [2,11]. Таким образом, коррекция ЭД может считаться одной из основных стратегий лекарствен-ной терапии нарушения мозгового кровообращения [11].…”
unclassified
“…Генера-ция активных форм кислорода (АФК) вызывает повреж-дение функционально активных молекул, таких как ли-пиды, белки и ДНК. При этом существенна окислитель-ная модификация клеток сосудистого эндотелия, приводящая к развитию эндотелиальной дисфункции (ЭД) [11]. В условиях инсульта формирование ЭД при-водит к ухудшению церебральной микроциркуляции, повышенному тромбообразованию, индукции воспале-ния и пролиферации сосудистой стенки, что усугубляет течение заболевания и снижает шансы на его благо-приятный исход [2,11].…”
unclassified
See 1 more Smart Citation